Optimal : how to sustain personal and organizational excellence every day - Goleman, Daniel, author (UK: Penguin Business, 2024)
"A book on emotional intelligence in organizations"-- Provided by publisher.
Keywords: Emotional intelligence; Organizational behavior; Management -- Psychological aspects